Successful extracorporeal membrane oxygenation support for severe acute diquat and glyphosate poisoning: A case report. Issue 6 (February 2019) - Wang, Danqiong; Zhang, Guozheng; Zhang, Weiwen; Luo, Jian; Zhu, Lihua; Hu, Jianhua
Abstract: Rationale: Because of the lack of an antidote or effective treatment, patients with severe acute diquat and glyphosate poisoning always died within a few hours. Extracorporeal membrane pulmonary oxygenation (ECMO), as an artificial heart-lung supporting system, can be applied to support lung that is expected to recover from reversible pathological damage. However, to our knowledge, the application of ECMO for patients with diquat and glyphosate poisoning has not been reported. Patient concerns: A 40-year-old man ingested in 100 ml of diquat (20 g/100 ml) and 400 ml glyphosate (41 g/100 ml) was admitted to the intensive care unit (ICU), immediately complicated by the development of ventricular fibrillation, respiratory failure, renal failure, and multi-organ failure. Diagnosis: Diquat and glyphosate poisoning were diagnosed by stated ingestion history, and the diagnostic criteria for acute respiratory distress syndrome (ARDS) and multi-organ dysfunction syndrome were also met. Interventions: He was treated with veno-venous ECMO. Outcomes: He was successfully transferred out of the ICU on day 46 and discharged on day 67. The computed tomography scan showed no obvious pulmonary fibrosis 2 months after poisoning. Lessons: ECMO may be effective in the treatment of patients with severe ARDS caused by diquat and glyphosate poisoning when conventional management does not work.